Azo Containing Thiophene Based Prop-2-enoates for Photoalignment of a Nematic Liquid Crystal - Hegde, Gurumurthy; Ata Alla, Rasha; Matharuc, Avtar; Komitov, Lachezar (Royal Society of Chemistry, 2013)
The ability of suitably derived prop-2-enoates from 3-(thiophen-2-yl)- and 3-(thiophen-3-yl)-prop-2-enoic acid and appropriately fluorinated and non-fluorinated 4-[(4-alkoxyphenyl)diazenyl]phenols to promote excellent photoalignment of a bulk commercial nematic liquid crystal is reported. The performed study showed that the photoalignment of the liquid crystal is influenced by the number and disposition of fluoro-substituents and the position of attachment of the terminal thiophene moiety, either 2- or 3-substituted, in the molecular structure of the alignment material. Inclusion of a lateral fluorosubstituent(s) induces an excellent photoalignment whereas the non-fluorinated counterpart tends to give an unsatisfactory alignment. 3-Substituted thiophenes give a better photoalignment than their 2-substituted isomeric counterparts. A prototype display, which contains an alignment layer made from one of the proposed materials, possessing good alignment ability, is presented in order to demonstrate the application potential of these materials in LCDs.